Local and regional determinants of vascular epiphyte mortality in the Andean mountains of Colombia. (11th March 2016) - Zuleta, Daniel; Benavides, Ana M.; López‐Rios, Victor; Duque, Alvaro
Summary: We present the first large‐scale assessment of vascular epiphyte mortality in the neotropics. Our goals were to explore the primary types of vascular epiphyte death and to identify local and regional determinants of epiphyte mortality in natural forests located 60 to 2900 m a.s.l. in the Colombian Andes. Based on two consecutive annual surveys, we followed the fate of 4247 epiphytes to estimate the epiphyte mortality rate on 116 host trees at nine sites. A logistic regression analysis for proportional data with a binomial distribution of the error was applied to determine the probability of epiphyte death in relation to local and regional explanatory variables. The overall epiphyte mortality rate was 7.5 ± 1.1% year −1 (mean ± standard error). Non‐mechanical factors, such as desiccation, accounted for a mortality rate of 1.9 ± 0.3% year −1 . Mechanical factors, such as falling branches, accounted for a mortality rate of 5.6 ± 1.1% year −1 . According to generalized linear modelling analyses, both local and regional factors played key roles in determining epiphyte mortality. The actual evapotranspiration (regional factor) and the mean epiphyte attachment height (local factor) were both consistently positively associated with the probability of epiphyte death. Additional variables identified as possible determinants of the epiphyte mortality were the temperature seasonality, annual temperature range, the height and number of branches of the tree and the abundance of large trees (DBH ≥10 cm). Synthesis . The recorded high mortality rate indicates that natural epiphyte assemblages must be highly dynamic to avoid local extinction of species. Our study identifies actual evapotranspiration as an important driver of epiphyte mortality, and we highlight its importance in determining the fate tropical epiphyte communities may experience if evapotranspiration increases due to climate change. We hope our study addresses the paucity of research on non‐tree growth forms, typically ignored in vegetation dynamics, and encourages their inclusion in future studies that investigate the function of tropical ecosystems. Abstract : We present the first large‐scale assessment of vascular epiphyte mortality in the neotropics. A recorded high mortality rate indicates that natural epiphyte assemblages must be highly dynamic to avoid local extinction of species. We hope this study will encourage the inclusion of non‐tree growth forms in future studies that investigate the function of tropical ecosystems. Photography by Samuel Monsalve.